No evidence for differences in the Epstein-Barr virus genome carried in Burkitt lymphoma cells and nonmalignant lymphoblastoid cells from the same patients. - Bornkamm, G W (1984)
Epstein-Barr virus (EBV), although not an indispensable factor for the development of Burkitt lymphoma, is apparently associated with the 20-fold higher incidence of the disease in Equatorial Africa compared to the incidence in other parts of the world. To determine whether different EBV subtypes are associated with the appearance of the malignant phenotype, we have compared the EBV genomes carried in the Burkitt tumor cells with those carried in the nonmalignant lymphoblastoid cells from the same individuals. From three patients with EBV -associated Burkitt lymphoma, tumor cell lines as well as spontaneously established lymphoblastoid cell lines representing the nonmalignant counterparts were obtained. The viral DNA in these cell lines was analyzed by Southern blot hybridization, using a set of cloned EBV DNA fragments as probes that recognize polymorphic regions in the viral genome. Using a number of different polymorphic markers to distinguish one isolate from another, the virus genome found in the tumor cells could also be identified in the nonmalignant cells of the same patient. In one case, in which two independent lymphoblastoid cell lines were established, evidence was obtained that this patient was infected by at least two distinct EBV subtypes. These results strongly suggest that in Burkitt lymphoma, the risk associated with EBV is related to cofactors such as chronic malaria and the mode of infection rather than to peculiar viral subtypes. The situation seems to be totally different from papillomavirus-associated diseases, in which the risk of progression to malignancy appears to be associated with particular viral strains.